HR in The Age of Artificial Intelligence: Managing Collaboration Between People and Technology - Jusup, Sri Meike; Rosalia, Olyvia; Harahap, Kamila (Maneggio, 2025)
This study aims to analyze the factors influencing the effectiveness of collaboration between humans and artificial intelligence (AI) in human resource (HR) management. Using a quantitative descriptive and explanatory approach, the research involved respondents from diverse job backgrounds who have interacted with AI systems in the workplace. The variables examined include digital literacy, trust in AI, training and development, and HR policies related to technology. Results from multiple linear regression analysis indicate that trust in AI is the most dominant factor driving effective collaboration, followed by training and digital literacy. In contrast, HR policies were not found to have a significant impact unless accompanied by clear implementation and communication. These findings highlight the importance of a human-centered approach in integrating technology into the workplace. The study contributes to the growing literature on technology-driven HR practices, particularly within the context of developing countries.